Optical Auroral Forms over Maitri during Antarctic winter 1994 and Their relationship with simultaneous geomagnetic variations - Hanchinal, A.N.; Sridharan, M.; Rajaram, G. (1997)
During the Antarctic winter of 1994 (Apr-Oct), the Indian Institute of Geomagnetism carried out one man campaign of auroral photography over the Indian stations MAITRI(MAI) and DAKSHIN GANGOTRI(DG). The idea was to study the direction in which the phenomenon of "aurora australis" originated and moved with respect to MAI and DG, and the changes which occurred in its colour, form and structure. Since all-sky cameras and Video/TV cameras were not available, the photographs were taken outdoors on a stand mounted ZENITH ET camera using 400 ASA Kodak film and exposure times of 8 to 15 sec. The other investigation was to see how the changes in aurora corresponded with simultaneous variations in the Y, X and Z components of the geomagnetic field, using both Daily Variation (DV) and electronically filtered Micropulsation (MP) magnetograms. Two events, namely a Harang Discontinuity which occurred over DG on 29 Apr 1994, and a fluted band auroral display over MAI on 20 Aug 1994, are selected for this study. Clear correlations seen between variations in the auroral forms and geomagnetic components are discussed, and periodicities observed in geomagnetic pulsations are brought out.